Corporate Social Responsibility- Need of the hour - Kour, Manjit; Aggarwal, Vimal Kumar (Gyan Management Journal, 2013)
Society has not only sanctioned business to operate accordin9 to the profit motive; at the same time business is expected to comply with the laws and regulations promulgated by federal, state, and local governments as the ground ailes under which business must operate. No longer is it acceptable simply to make good products that satisfy customers while complying with laws and regulations. But businesses are also expected to formulate and implement-social goals and programs as well as integrate ethical sensitivity into all decision making. Social responsibility means eliminating corrupt, irresponsible or unethical behavior which might bring harm to the community, its people and the environment Social responsibility is voluntary. It is about going above and beyond what is called for by the law. The demands for greater social responsibility are coming from mainstream quarters of society, as well as protesters at global meetings. Firms must formulate and implement-social goals and programs as well as inte9rate ethical sensitivity into all decision making, policies, and actions. This paper is an attempt to understand the concept of CSR, examine the pressures for increased corporate attention to CSR and its si9nificance.
Keywords: Society; business; federal; local governments; voluntary; CSR